Praktik Jurnalisme Bencana pada Program Kentongan RRI Madiun - Annisa Hudayatus Shofa; Eli Purwati; Deny Wahyu Tricana (Program Studi Ilmu Komunikasi FBIK Unissula, 2023)
Indonesia is a country with a high potential for disaster. In 2021 BNPB recorded 5,402 disasters had occurred in Indonesia. Indonesian people need education and information about disasters and how to prevent them. Disaster and its impacts can be informed through the mass media to the public. One of them is Radio which provides efficiency and effectiveness in delivering information about the risks and impacts of disasters, epidemics, and other disasters. In response to this situation, RRI presented a broadcast program